Retinal pharmacotherapy - Nguyen, Quan Dong.; ScienceDirect eBooks ([Maryland Heights, MO] : Saunders/Elsevier, 2010)
Retinal Pharmacotherapy is the first comprehensive book devoted to pharmacologic agents and their rationale and mechanisms of action in selected retinal and uveitic diseases. Drs. Quan Dong Nguyen, Eduardo Buchele Rodrigues, Michel Eid Farah, and William F. Mieler lead an international team of expert contributors to present up-to-date knowledge of new drugs on the market, the science behind the drugs, evidence of how the drugs work, and the reasons why they are effective or not. This user-friendly, all-in-one reference provides you with easy access to practical information on the effective and appropriate use of pharmacologic agents in the management of retinal diseases. Covers all new and existing retinal drugs to keep you current in this expanding area of the treatment of retinal diseases. Discusses the background behind retinal drugs and the various pathways of how they work so you can make thoroughly informed clinical decisions. Presents 400 color photographs and line drawings that illustrate disease appearance before and after treatment and clarify difficult key concepts. Features contributors from Europe, North America, South America, the Middle East, Asia, and Australia for an international approach. Identifies and emphasizes key points clearly in each chapter to improve comprehension and make finding information easier.
Evolving Knowledge in Pharmacologic Treatments -- Section 1. Basic Sciences in Retina -- Retinal Anatomy and Pathology -- Retinal Biochemistry, Physiology and Cell Biology -- Ocular Angiogenesis: Vascular Endothelial Growth Factor and Other Factors -- Ocular Immunity and Inflammation -- Complement Activation and Inhibition in Retinal Disease -- Genetics of Retinal Disease --Section 2. Animal Models and Routes for Retinal Drug Delivery -- Vitamins and Supplements for Age-Related Macular Degeneration -- Ocular Pharmacokinetic, Drug Bioavailability and Intraocular Drug Delivery Systems 0 Routes for Drug Delivery to the Eye and Retina: Intravitreal Injections and Vitrectomy -- Routes for Drug Delivery: Topical, Transscleral, Suprachoroidal, and Intravitreal Gas-Phase Nanoparticles -- Routes for Drug Delivery: Sustained-Release Devices -- Microspheres and Nanotechnology for Drug Delivery -- Thermo-sensitive Hydrogels -- Retina and Ocular Toxicity to Ocular Application of Drugs -- Retinal Toxicity of Systemic and Topical Medications -- Section 3. Retinal Diseases Amenable to Pharmacotherapy -- Non-neovascular Age-Related Macular Degeneration -- Neovascular Age-Related Macular Degeneration -- Diabetic Retinopathy and Diabetic Macular Edema -- Retinal Vein Occlusion -- Retinal Detachment and Proliferative Vitreoretinopathy -- Posterior Uveitis -- Choroidal Neovascularization Secondary to Inflammation, Infection, and Myopia -- Ocular Infection: Endophthalmitis -- Retinopathy of Prematurity -- Idiopathic Macular Telangiectasia -- Neovascular Glaucoma -- Retinal Hereditary and Degenerative / Dystrophic Diseases (non-AMD) -- Section 4. Drugs and Mechanisms in Retinal Diseases -- Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) in the Treatment of Retinal Diseases -- Corticosteroids: Triamcinolone, Dexamethasone, Fluocinolone, and Others -- Anecortave Acetate -- Therapeutic Monoclonal Antibodies and Fragments: Bevacizumab -- Therapeutic Monoclonal Antibodies and Fragments: Ranibizumab -- Pathophysiology of Vascular Endothelial Growth Factor and Other Angiogenic Molecules -- Biologic Therapies: Infliximab, Adalimumab, Etanercept, Daclizumab, and Others -- Immunomodulatory Therapy in Uveitis -- Fusion Proteins: VEGF-Trap -- Aptamers and Intramers: Pegaptanib -- Protein Kinase C Inhibitor: Ruboxistaurin -- Small-Interference RNA Technology: SIRNA 027, Bevasiranib, and REDD14NP -- Ocular Gene Therapy -- Neuroprotection and Retinal Diseases -- Photosensitizers and Photodynamic Therapy: Verteporfin -- Chemotherapy for Malignant Intraocular Tumors -- Antibiotics -- Section 5. Pharmacotherapy and Surgery -- Rheotherapy (Rheopheresis; Therapeutical Apheresis) -- Enzymatic Vitrectomy and Pharmacologic Vitreodynamics -- The Use of Vital Dyes during Vitreoretinal Surgery -- Chromovitrectomy -- Epimacular and External Radiotherapy -- Current Status of Human Retinal Pigment Epithelial Transplantation -- Section 6. The Last Words -- Off-Label Drugs and the Impact of the Food and Drug Administration in the Treatment of Retinal Disease -- Value-Based Medicine and Pharmacoeconomics -- Future Perspectives: Agents on the Horizon.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Retina -- Diseases -- Chemotherapy; HEALTH & FITNESS -- Vision; MEDICAL -- Ophthalmology; Retina -- drug effects; Retinal Diseases -- drug therapy; Electronic books